1972
DOI: 10.1083/jcb.54.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Vesicles From Frog Neuromuscular Junctions by Prolonged Tetanic Stimulation

Abstract: A B S T R A C TCurarized cutaneous pectoris nerve muscle preparations from frogs were subjected to prolonged indirect stimulation at 2/see while recording" from end plate regions. At the ends of the periods of stimulation, the curare was removed and the preparations were fixed for electron microscopy or treated with black widow spider venom to determine the degree to which their stores of transmitter had been depleted. After 6--8 hr of stimulation the nerve terminals were almost completely depleted of their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
175
2
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(190 citation statements)
references
References 9 publications
11
175
2
2
Order By: Relevance
“…Hence, ACh synthesis at rest may not be inhibited by HC-3 either because HC-3 does not have access to the sites of synthesis or because the synthesis is not dependent on extracellular choline. In stimulated diaphragms, however, newly synthesized ACh is preferentially released (9), perhaps because it is used to reload recycled vesicles (6,7,18,37). This synthesis may occur only in highly restricted regions of the terminal immediately adjacent to the sites of ACh release (10) and may be critically dependent on choline supplied by a high-affinity transport system (15).…”
Section: Gomo Et Al Acetylcholine Compartments In Mouse Diaphragmmentioning
confidence: 99%
“…Hence, ACh synthesis at rest may not be inhibited by HC-3 either because HC-3 does not have access to the sites of synthesis or because the synthesis is not dependent on extracellular choline. In stimulated diaphragms, however, newly synthesized ACh is preferentially released (9), perhaps because it is used to reload recycled vesicles (6,7,18,37). This synthesis may occur only in highly restricted regions of the terminal immediately adjacent to the sites of ACh release (10) and may be critically dependent on choline supplied by a high-affinity transport system (15).…”
Section: Gomo Et Al Acetylcholine Compartments In Mouse Diaphragmmentioning
confidence: 99%
“…For example, in neurohypophysis (13), anterior pituitary (20), adrenal medulla (1), peripheral nerve terminals (5,27), and islet cells (36), it has been suggested that membrane components delivered to the cell surface during the exocytosis of the secretory granule are retrieved by the cell through a burst of pinocytic activity. This hypothesis has not been tested quantitatively, but a stereologic analysis with HRP migh be a useful means of doing so.…”
Section: Recycling Of Pinocytosed Membranementioning
confidence: 99%
“…Recruitment comes from synaptic vesicles that can reside several vesicle diameters away from fusion sites (Ceccarelli et al, 1972). Directed transport via an actin-myosin mechanism has been proposed to facilitate movement, based primarily on evidence of myosin involvement in vesicle recruitment (Prekeris and Terrian, 1997;Ryan, 1999;Verstreken et al, 2005) (but see Tokuoka and Goda, 2006).…”
Section: Introductionmentioning
confidence: 99%